On non-linear W-infinity symmetry of generalized Liouville and conformal Toda models - Aratyn, H.; Ferreira, L. A. [UNESP]; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP] (Elsevier, 1993)
Invariance under non-linear Ŵ∞ algebra is shown for the two-boson Liouville type of model and its algebraic generalizations, the extended conformal Toda models. The realization of the corresponding generators in terms of two boson currents within KP hierarchy is presented.